1996
DOI: 10.1111/j.1365-2710.1996.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological modification of cardiac risk factors: part 1

Abstract: SUMMARYMany fadors influence whether a person will develop coronary heart disease. Genetic predisposition, gender and advanced age are recognized risk factors for the development of coronary heart disease over which we have little control. On the other hand, high serum cholesterol, cigarette smoking, high blood pressure, excessive body weight and long-term physical inactivity are key risk factors over which we have considerable control. In many cases cardiac risk factors can be modified without resorting to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The risk factors associated with CHD are multifactorial and work synergistically. Genetic predisposition, sex (it is more common in males), family history of ischaemic heart disease (especially in a first-degree relative under 55 years), stroke, peripheral vascular disease and advanced age are recognized risk factors for the development of CHD over which there is little control [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors associated with CHD are multifactorial and work synergistically. Genetic predisposition, sex (it is more common in males), family history of ischaemic heart disease (especially in a first-degree relative under 55 years), stroke, peripheral vascular disease and advanced age are recognized risk factors for the development of CHD over which there is little control [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that aggressive risk factor modification can lower plasma lipid concentrations, reverse atherosclerosis and substantially diminish acute cardiac events in patients who already have the disease (DeBusk, 1996;Maines et al, 1997;Eagles and Gulati, 1996). Traditionally the role of the patient in the health care system has been characterised as essentially passive, demanding that patients place the responsibility for their health in the hands of health care professionals (Mahler and Kulik, 1990).…”
mentioning
confidence: 99%
“…There are many factors that contribute to the development of CAD 3,5,12–15 . In order to retard the progression of this disease sustained lifestyle modifications are of paramount importance for the individuals concerned 4,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, lifestyle pattern change for CAD sufferers remains essential if rehabilitation measures are to decrease the likelihood of a second potentially more severe MI following a PTCA/stent procedure 3,12 . Despite evidence regarding what lifestyle factors require change, a significant number of MI victims still do not make any lifestyle changes 3,5,12–15 . Currently, the literature describes numerous risk factors associated with CAD and the lifestyle behaviours required for a healthy heart.…”
Section: Introductionmentioning
confidence: 99%